Selective ring-opening metathesis polymerization (ROMP) of cyclobutenes. Unsymmetrical ladderphane containing polycyclobutene and polynorbornene strands - Ke, Yuan-Zhen; Huang, Shou-Ling; Lai, Guoqiao; Luh, Tien-Yau (Beilstein Journal of Organic Chemistry, 2019)
At 0 °C in THF in the presence of Grubbs first generation catalyst, cyclobutene derivatives undergo ROMP readily, whereas norbornene derivatives remain intact. When the substrate contains both cyclobutene and norbornene moieties, the conditions using THF as the solvent at 0 °C offer a useful protocol for the selective ROMP of cyclobutene to give norbornene-appended polycyclobutene. Unsymmetrical ladderphane having polycyclobutene and polynorbornene as two strands is obtained by further ROMP of the norbornene appended polycyclobutene in the presence of Grubbs first generation catalyst in DCM at ambient temperature. Methanolysis of this unsymmetrical ladderphane gives polycyclobutene methyl ester and insoluble polynorbornene-amide-alcohol. The latter is converted into the corresponding soluble acetate. Both polymers are well characterized by spectroscopic means. No norbornene moiety is found to be incorporated into polycyclobutene strand at all. The double bonds in the polycyclobutene strand are mainly in cis configuration (ca 70%), whereas the E/Z ratio for polynorbornene strand is 8:1.
Keywords: cyclobutene; hydrolysis; linker; metathesis; norbornene; ROMP; selectivity; unsymmetrical ladderphane

Synthesis of Polymers - Buchmeiser, M. R. (Chapter 19, 2012)

(untitled) - Buchmeiser, M. R. (Chem. Rev., 2000)

Handbook of Metathesis. Polymer Synthesis - Grubbs., R. H.; Khosravi, E. (Wiley-VCH, 2015)

(untitled) - Luh, T.-Y. (Acc. Chem. Res., 2013)

(untitled) - Luh, T.-Y.; Ding, L. (Tetrahedron, 2017)

(untitled) - Yang, H.-C.; Lin, S.-Y.; Yang, H.-C.; Lin, C.-L.; Tsai, L.; Huang, S.-L.; Chen, I. W.-P.; Chen, C.-h.; Jin, B.-Y.; Luh, T.-Y. (Angew. Chem., Int. Ed., 2006)

(untitled) - Yang, H.-C.; Lee, S.-L.; Chen, C.-h.; Lin, N.-T.; Yang, H.-C.; Jin, B.-Y.; Luh, T.-Y. (Chem. Commun., 2008)

(untitled) - Chou, C.-M.; Lee, S.-L.; Chen, C.-H.; Biju, A. T.; Wang, H.-W.; Wu, Y.-L.; Zhang, G.-F.; Yang, K.-W.; Lim, T.-S.; Huang, M.-J.; Tsai, P.-Y.; Lin, K.-C.; et al. (J. Am. Chem. Soc., 2009)

(untitled) - Yang, K.-W.; Xu, J.; Chen, C.-H.; Huang, H.-H.; Yu, T. J.-Y.; Lim, T.-S.; Chen, C.-h.; Luh, T.-Y. (Macromolecules, 2010)

(untitled) - Chen, C.-W.; Chang, H.-Y.; Lee, S.-L.; Hsu, I.-J.; Lee, J.-J.; Chen, C.-h.; Luh, T.-Y. (Macromolecules, 2010)

(untitled) - Wang, H.-W.; Chen, C.-H.; Lim, T.-S.; Huang, S.-L.; Luh, T.-Y. (Chem. – Asian J., 2011)

(untitled) - Huang, H.-H.; Chao, C.-G.; Lee, S.-L.; Wu, H.-J.; Chen, C.-h.; Luh, T.-Y. (Org. Biomol. Chem., 2012)

(untitled) - Yeh, N.-H.; Chen, C.-W.; Lee, S.-L.; Wu, H.-J.; Chen, C.-h.; Luh, T.-Y. (Macromolecules, 2012)

(untitled) - Xu, J.; Zhang, Z.; Liu, Y.-H.; Guo, Q.; Wang, G.-W.; Lai, G.; Luh, T.-Y. (J. Polym. Sci., Part A: Polym. Chem., 2017)

(untitled) - Zhu, L.; Flook, M. M.; Lee, S.-L.; Chan, L.-W.; Huang, S.-L.; Chiu, C.-W.; Chen, C.-H.; Schrock, R. R.; Luh, T.-Y. (Macromolecules, 2012)

(untitled) - Chen, C.-H.; Satyanarayana, K.; Liu, Y.-H.; Huang, S.-L.; Lim, T.-S.; Luh, T.-Y. (Chem. – Eur. J., 2015)

(untitled) - Zhu, L.; Lin, N.-T.; Xie, Z.-Y.; Lee, S.-L.; Huang, S.-L.; Yang, J.-H.; Lee, Y.-D.; Chen, C.-h.; Chen, C.-H.; Luh, T.-Y. (Macromolecules, 2013)

(untitled) - Lin, N.-T.; Xie, C.-Y.; Huang, S.-L.; Chen, C.-H.; Luh, T.-Y. (Chem. – Asian J., 2013)

(untitled) - Lin, N.-T.; Lin, S.-Y.; Lee, S.-L.; Chen, C.-h.; Hsu, C.-H.; Hwang, L. P.; Xie, Z.-Y.; Chen, C.-H.; Huang, S.-L.; Luh, T.-Y. (Angew. Chem., Int. Ed., 2007)

(untitled) - Lai, G.; Luh, T.-Y. (Bull. Chem. Soc. Jpn., 2018)

(untitled) - Ke, Y.-Z.; Lee, S.-L.; Chen, C.-h.; Luh, T.-Y. (Chem. – Asian J., 2011)

(untitled) - Ke, Y.-Z.; Ji, R.-J.; Wei, T.-C.; Lee, S.-L.; Huang, S.-L.; Huang, M.-J.; Chen, C.-h.; Luh, T.-Y. (Macromolecules, 2013)

(untitled) - Moatsou, D.; Hansell, C. F.; O'Reilly, R. K. (Chem. Sci., 2014)

Sequence-Controlled Polymers - Lutz, J.-F. (Wiley-VCH Verlag GmbH, 2018)

(untitled) - Wu, Z.; Wheeler, D. R.; Grubbs, R. H. (J. Am. Chem. Soc., 1992)

(untitled) - Wu, Z.; Grubbs, R. H. (Macromolecules, 1994)

(untitled) - Perrott, M. G.; Novak, B. M. (Macromolecules, 1995)

(untitled) - Perrott, M. G.; Novak, B. M. (Macromolecules, 1996)

(untitled) - Maughon, B. R.; Grubbs, R. H. (Macromolecules, 1997)

(untitled) - Charvet, R.; Novak, B. M. (Macromolecules, 2001)

(untitled) - Lee, J. C.; Parker, K. A.; Sampson, N. S. (J. Am. Chem. Soc., 2006)

(untitled) - Song, A.; Parker, K. A.; Sampson, N. S. (J. Am. Chem. Soc., 2009)

(untitled) - Parker, K. A.; Sampson, N. S. (Acc. Chem. Res., 2016)

(untitled) - Lin, N.-T.; Ke, Y.-Z.; Satyanarayana, K.; Huang, S.-L.; Lan, Y.-K.; Yang, H.-C.; Luh, T.-Y. (Macromolecules, 2013)

Strained organic molecules - Greenberg, A.; Liebman, J. F. (Academic Press, 1978)

(untitled) - Schwab, P.; Grubbs, R. H.; Ziller, J. W. (J. Am. Chem. Soc., 1996)

(untitled) - Rule, J. D.; Moore, J. S. (Macromolecules, 2002)

(untitled) - Wenzel, A. G.; Grubbs, R. H. (J. Am. Chem. Soc., 2006)

N-Heterocyclic Carbenes in Synthesis - Beligny, S.; Blechert, S. (Wiley-VCH, 2006)

(untitled) - van der Eide, E. F.; Piers, W. E. (Nat. Chem., 2010)

(untitled) - Cazalis, C.; Héroguez, V.; Fontanille, M. (Macromol. Chem. Phys., 2000)

(untitled) - Al Samak, B.; Amir-Ebrahimi, V.; Corry, D. G.; Hamilton, J. G.; Rigby, S.; Rooney, J. J.; Thompson, J. M. (J. Mol. Catal. A: Chem., 2000)

(untitled) - Matos, J. M. E.; Lima-Neto, B. S. (J. Mol. Catal. A: Chem., 2005)

(untitled) - Sattigeri, J. A.; Shiau, C.-W.; Hsu, C. C.; Yeh, F.-F.; Liou, S.; Jin, B.-Y.; Luh, T.-Y. (J. Am. Chem. Soc., 1999)

(untitled) - Lin, W.-Y.; Murugesh, M. G.; Sudhakar, S.; Yang, H.-C.; Tai, H.-C.; Chang, C.-S.; Liu, Y.-H.; Wang, Y.; Chen, I.-W. P.; Chen, C.-h.; Luh, T.-Y. (Chem. – Eur. J., 2006)

(untitled) - Lin, W.-Y.; Wang, H.-W.; Liu, Z.-C.; Xu, J.; Chen, C.-W.; Yang, Y.-C.; Huang, S.-L.; Yang, H.-C.; Luh, T.-Y. (Chem. – Asian J., 2007)